Factors Influencing Behavioral Intentions for Leave No Trace Behavior in National Parks. Issue 1 (April 2013) - Lawhon, Ben; Newman, Peter; Taff, Derrick; Vaske, Jerry; Vagias, Wade; Lawson, Steve; Monz, Christopher
Resource degradation resulting from visitor behavior continues to be a significant concern for land managers, and effective educational messages such as those promoted through Leave No Trace, which target depreciative behaviors, are imperative. This study examined psychological and knowledge variables that were hypothesized to influence future Leave No Trace behavioral intent of visitors in Rocky Mountain National Park. Data were obtained from an on-site survey administered to individuals ( n = 390, response rate 74%) in the Bear Lake corridor of the park. Results of a multiple regression analysis revealed that perceived effectiveness of Leave No Trace practices is a significant predictor of future behavioral intent (β > .21, p < .001, in all cases). Frontcountry visitors like those at Bear Lake are more likely to practice Leave No Trace if they perceive the practices to be effective at reducing impacts.